The Effectiveness, Efficiency, and Appeal of Pediatric Echocardiography Protocol Training for First Year Pediatric Cardiology Fellows - (:unkn) unknown (My University, 2016)
Echocardiography training for pediatric cardiology fellows is complex and academic hospitals strive to provide high-quality training using limited resources. The purpose of this embedded single case study design was to evaluate the effectiveness, efficiency, and appeal of a newly developed 10-day echocardiography protocol learning module for first year pediatric cardiology fellows. Using blended learning methods that included didactic lectures, online learning activities, and interactive games, the learning module was the first step in the process of training pediatric cardiology fellows to perform echocardiograms independently with limited supervision during their first year of fellowship. At the end of the 10-day module, the cardiology fellows successfully learned the pediatric echocardiography protocol and were able to begin applying their new knowledge in the echocardiography laboratory. Results from the qualitative evaluation confirmed that the learning module was effective, efficient, and appealing.
Keywords: Cardiology; Echocardiography; Education; Pediatric; Protocol